Analysis of Elementary School Student's Responses to Implementing the 2013 Curriculum Through Distance Learning During the Covid-19 Pandemic - Lenthera Mega Devya; Wiryanto Wiryanto (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2022)
The distance learning policy is the best effort to minimize the spread of Covid-19 in schools. This study aims to see the response of students in distance learning in the 2013 curriculum. The research method used is a descriptive quantitative method and the data source is obtained from questionnaires given to 156 students in 12 elementary schools spread across 7 regencies/cities of East Java. The results showed that 100 percent of students took distance learning as scheduled, 51.3 percent of students accompanied by mothers, 10.3 percent of students accompanied by fathers, 20.5 percent of students accompanied by guardians, and 17.9 percent of students had no companions while studying. The communication tools used showed that 92.9 percent used social media, 71.8 percent of students found it difficult to understand thematic learning, 49.4 percent of the student assignment collection places were social media, and 92.9 percent of students thought distance learning added to technological knowledge.